Periodic Table as a Constructivist Model of Teaching-learning at the Secondary Level - Arya, Anand Kumar; Pal, Narendra (SCHOOL SCIENCE, 2017)
The article demonstrates the use of periodic table as constructivist model of teaching-learning to understand the periodic trends among the elements. The focus of the activity is to shift the passive learner from rote memorisation and facilitates them to construct their own understanding of the fundamental concepts such as electronic configuration, atomicity and valency of elements, charges on the ion, recalling the atomic number of elements, etc.